‘Thinking’ terminologies from Qurónic perspective and their impact on human intellectual development - Badi, Jamal Ahmed Bashier (Inderscience Publishers, 2011)
The 'Qur'En' as a divine book has terms that are used and related to 'thinking' such as TaIawwur (conceiving), Idrak (perceiving), Fiqh (grasping), TaNaqqul (reasoning), Tadhakkur (contemplating) etc. This paper explores major Qur'Enic terms related to thinking with the aim of uncovering potential value of these terms for human life. For this purpose, both textual and contextual analyses have been applied, as appropriate. The paper argues that internalising the Qur'Enic terms for thinking will contribute to the uplift of the global struggle on formalisation of thinking in public and private places for rightful human thought. The positive influence of Qur'Enic thinking will not remain limited to individuals, but will also affect communities through influence of human thought and behaviour which, in turn, will lead to a paradigm shift in the academic realm.